Workshop Media Pembelajaran Berbasis Artificial Intelegence - Lestari, Dirga Ayu (STAI Publisistik Thawalib Jakarta, 2024)
The aim of this community service is to enhance teachers' creativity in utilizing Artificial Intelligence (AI) technology in teaching activities. The service method was conducted in-person, utilizing LCD Projectors and sound systems to support workshop activities. The results of the implementation show that teachers have gained an understanding of creating instructional media using Canva and CapCup. This is evident as teachers can operate both AI applications and produce instructional media that are sufficiently good and diverse. In conclusion, the workshop proceeded smoothly as scheduled, providing a positive impact on teachers.